2017
DOI: 10.1038/ncomms14610
|View full text |Cite
|
Sign up to set email alerts
|

PNPLA1 is a transacylase essential for the generation of the skin barrier lipid ω-O-acylceramide

Abstract: Lipids are the primary components of the skin permeability barrier, which is the body's most powerful defensive mechanism against pathogens. Acylceramide (ω-O-acylceramide) is a specialized lipid essential for skin barrier formation. Here, we identify PNPLA1 as the long-sought gene involved in the final step of acylceramide synthesis, esterification of ω-hydroxyceramide with linoleic acid, by cell-based assays. We show that increasing triglyceride levels by overproduction of the diacylglycerol acyltransferase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
110
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 103 publications
(117 citation statements)
references
References 41 publications
4
110
0
Order By: Relevance
“…Our genetic approach using knockout mice and the biochemical approach by Ohno et al 49. complement each other by providing different lines of evidence that prove that PNPLA1 catalyses the ω- O -esterification in acylceramide biosynthesis.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Our genetic approach using knockout mice and the biochemical approach by Ohno et al 49. complement each other by providing different lines of evidence that prove that PNPLA1 catalyses the ω- O -esterification in acylceramide biosynthesis.…”
Section: Discussionmentioning
confidence: 93%
“…The corresponding accumulation of putative precursors of these three lipid groups, namely ω-OH Cer, ω-OH GlcCer and ω-OH ULCFA, in PNPLA1-deficient epidermis provides strong evidence that PNPLA1 acts as an ω- O -acyltransferase or transacylase required for acylceramide synthesis. In this regard, the accompaning study by Ohno et al 49. has clearly shown that exogenous overexpression of PNPLA1 in cells or PNPLA1-reconstituted proteoliposomes promotes acylceramide formation likely as a transacylase and that PNPLA1 mutations associated with ARCI inactivate this transacylase activity.…”
Section: Discussionmentioning
confidence: 98%
“…Fragment (product) ions were detected in the scanning range m/z 100‐600. In MRM, ceramides were detected by setting the Q1 m/z value at [M + H − H 2 O] + for the precursor ions and the Q3 m/z value as that specific to SPH ( m/z 264.3) or SPD‐specific fragment ions ( m/z 262.3), using the appropriate collision energies (Tables ), as described previously . Data analyses were performed using MassLynx software (Waters).…”
Section: Methodsmentioning
confidence: 99%
“…Lipids corresponding to 5 µg of brain tissue [for GalCer, 2‐hydroxy (2‐OH) GalCer, sulfatide, and ceramide] or 0.5 µg of brain tissue (for sphingomyelin) were subjected to liquid chromatography (LC)–tandem mass spectrometry (MS/MS) analysis using an ultra‐performance LC–triple‐quadrupole mass spectrometry system (Xevo TQ‐S; Waters), as described previously . Lipids were resolved on a reverse‐phase column (ACQUITY UPLC CSH C18 column; 1.7 µm particle size, 2.1 × 100 mm; Waters), ionized by electrospray ionization in positive ion mode, and detected using multiple reaction monitoring by selecting the specific m/z at quadrupole mass filters Q1 and Q3 and using the appropriate collision energy for each GalCer, 2‐OH GalCer, sulfatide, sphingomyelin, and ceramide species (Tables ).…”
Section: Methodsmentioning
confidence: 99%